Sleep-Related Eating Disorders - Auger, R. Robert (Matrix Medical Communications, 2006)
Although they share similar features, there are important differences between nocturnal eating syndrome and sleep-related eating disorder, which can be elucidated with a careful history and evaluation. While the former is best characterized as an eating disorder with associated insomnia, the latter is classified as a parasomnia, and is frequently affiliated with other primary sleep disorders. Nonsomatic therapies in isolation do not appear to be helpful for either condition, but effective pharmacotherapies have been described for both entities. Beyond the obvious discouragement and social embarrassment conferred by both conditions, there are also significant potential medical comorbidities, predominantly in the form of refractory obesity and related complications.